UNDIED LOVE: THE DIALOGUE BETWEEN I CORINTHIANS 11:23-25 WITH GRAVES IN SANGIHE THROUGH THE LENS OF THEOLOGY OF REMEMBRANCE - Ryanto Adilang; Andrea Elfata Ratulangi (DA'AT : Jurnal Teologi Kristen, 2025)
It should be understood that everything always comes with a risk. This applies to everything, from the simple to the most complex. Risk is even present in the effort to love and be loved by someone. The most painful risk of loving is when death comes to pick you up. The Sangihe community seems to have its own way to deal with this. However, this method has drawn pros and cons from many circles, namely by choosing an unusual location for a grave (near one's own residence). This study uses qualitative research methods and Theology of Remembrance theory as the main "surgical section". Through Theology of Remembrance, the researcher examines the Bible text from I Corinthians 11:23-25 ​​and the customs of the Sangihe community in choosing a burial location. After that, these two studies were dialogued to find the strategies of Paul and the Sangihe community in an effort to remember honestly and make peace with the past. This research is expected to reveal the secret behind the habits of the Sangihe people when choosing a burial location and the philosophy behind the habit. The habit of making a grave near the residence/house is an effort by the Sangihe people to remember the past peacefully, both good and bad memories.